2015
DOI: 10.5539/jfr.v4n6p104
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Consumer Acceptability of Spiced Black Tea

Abstract: Value addition of bulk curl tear cut (CTC) black tea is important to meet emerging customer needs and address challenges in a competitive beverage market. Spicing of the tea is one way of value addition but little or no research has been done on the biochemical effect of blending tea with spices and consumer acceptability. A study was conducted to determine the effect of spices on consumer acceptability; pricing and anti-oxidant capacities of black CTC tea consumed in the Kenyan market. Six spices and a spice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The addition of cinnamon at 10%, lemon grass at 10% and nutmeg at 25% improved sensory attributes of purple tea variety with mean values of 6.88, 6.24 and 6.92, respectively, on a hedonic scale . In addition, a study conducted by Ochanda et al . revealed that while spicing increased the enjoyment of black tea, there was no significant difference in the hedonic scale of preference of the three blends of tea (black tea spiced with either ginger, lemon grass or cinnamon) by consumers.…”
Section: Blending Of Teas As a Means Of Enhancing Sensory Attributesmentioning
confidence: 99%
“…The addition of cinnamon at 10%, lemon grass at 10% and nutmeg at 25% improved sensory attributes of purple tea variety with mean values of 6.88, 6.24 and 6.92, respectively, on a hedonic scale . In addition, a study conducted by Ochanda et al . revealed that while spicing increased the enjoyment of black tea, there was no significant difference in the hedonic scale of preference of the three blends of tea (black tea spiced with either ginger, lemon grass or cinnamon) by consumers.…”
Section: Blending Of Teas As a Means Of Enhancing Sensory Attributesmentioning
confidence: 99%
“…Teh dapat dijadikan bahan dasar inovasi pengembangan produk minuman fungsional salah satunya untuk diabetes. Penelitian terdahulu telah melaporkan tentang kombinasi minuman teh dengan beberapa bahan dari tumbuhan yang berbeda juga bagian tumbuhan yang berbeda seperti biji, bunga, buah, daun, dan batang bertujuan untuk meningkatkan nilai nutrisi dan nilai farmakologisnya (Namdev & Gupta, (2015); D'Ulivo (2018); Ochanda et al, (2015); Gulua et al, (2018)) atau membuat teh hijau atau teh hitam dari bahan lain seperti teh daun kelor, Withania somnifera, dan rosella (Oduro et al, (2013); Onyekwelu, C. N., Oragba, (2019); Okafor & Ogbobe, (2015); Namdev & Gupta, (2015). Kandungan senyawa polifenol pada teh merupakan suatu kelebihan tersendiri karena perannya sebagai penghambat reaksi oksidasi dan menangkap radikal bebas.…”
Section: Hasil Dan Pembahasanunclassified
“…Garam masala is commonly added to dishes to enhance their aroma. Spices are not only added to season dishes, but also widely used for beverages, for example black tea with garam masala (Ochanda et al, 2015). The use of garam masala which is rich in spices also serves as a preservative for the product.…”
Section: Introductionmentioning
confidence: 99%